Horrid Henry meets the queen - Simon; Francesca (London Dolphin Paperback, 2004)
Summary:In these four stories, the Queen is coming to visit Horrid Henry's school, he tries to hypnotise Moody Margaret, he tricks Perfect Peter into doing his household chores and Horrid Henry has a bath